2020
DOI: 10.7150/jca.37604
|View full text |Cite
|
Sign up to set email alerts
|

Application of metabolomics in the diagnosis of breast cancer: a systematic review

Abstract: Breast cancer (BC) remains the most frequent type of cancer in females worldwide. However, the pathogenesis of BC is still under the cloud, along with the huge challenge of early diagnosis, which is widely acknowledged as the key to a successful therapy. Metabolomics, a newborn innovative technique in recent years, has demonstrated great potential in cancer-related researches. The aim of this review is to look back on clinical and cellular metabolomic studies in the diagnosis of BC over the past decade, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 94 publications
1
62
0
Order By: Relevance
“…The development of metabolomics has dramatically expanded our understanding of the metabolic reprogramming that occurs in cancer—something that is now recognized as an important hallmark of tumors 276 . Metabolomics now represents an important new tool for noninvasive diagnosis and screening for cancer 277 . Tumors undergo lipid metabolic reprogramming that is strongly linked to malignant transformation and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The development of metabolomics has dramatically expanded our understanding of the metabolic reprogramming that occurs in cancer—something that is now recognized as an important hallmark of tumors 276 . Metabolomics now represents an important new tool for noninvasive diagnosis and screening for cancer 277 . Tumors undergo lipid metabolic reprogramming that is strongly linked to malignant transformation and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the metabolic pathways that are active in cancer cells, which allow the tumor to stay perfused and continue to grow, involve the production of biomarkers that can then be used to monitor tumor status and efficacy of therapies. These studies have indicated a correlation between metabolite profiles and disease in cancers, such as breast [54][55][56], endometrial [57], gastrointestinal (GI) [58], colorectal [59], head and neck [60], pancreatic [61,62], and bladder [63].…”
Section: Diseasementioning
confidence: 99%
“…[22][23][24][25] Similarly, plasma metabolites have been investigated as diagnostic and prognostic biomarkers in several diseases such as heart disease, 26 hepatitis, 27 Alzheimer's disease, 28 and cancer. 29,30 Similar to plasma glycans, plasma metabolites are biologically active molecules that function to regulate critical immunological responses, including in ammatory responses. [31][32][33][34] In a recent pilot study, 35 we identi ed several plasma glycomic structures whose pre-ATI levels associate with delayed viral rebound after ART discontinuation.…”
Section: Introductionmentioning
confidence: 99%